1995
DOI: 10.1108/00400919510088898
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing management information systems with practical restaurants in UK hospitality degree programmes

Abstract: The use of practical teaching restaurants as experiential learning resources is widely practised in UK institutions offering hospitality management programmes at undergraduate degree level. Surveys the extent to which students are permitted to make management decisions in such teaching restaurants. While some institutions give students considerable freedom to manage their restaurants, others give little opportunity to experience a realistic work environment. The use of computerized management information syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The latter result suggests that their supervisors have very high expectations of the hotel school trainees; in only two of the areas (shaded in Table 1), Positive attitude towards customers and positive attitude towards colleagues, did the trainees exceed the supervisors' average performance expectations, underpinning the quality of the Swiss system in developing people skills but also stressing the need for, and value of, the practical training as recommended by Morrison and Laffin (1995). No individual trainee's performance was rated outstanding in the initial stages of the internship by any of the supervisors in any of the areas.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The latter result suggests that their supervisors have very high expectations of the hotel school trainees; in only two of the areas (shaded in Table 1), Positive attitude towards customers and positive attitude towards colleagues, did the trainees exceed the supervisors' average performance expectations, underpinning the quality of the Swiss system in developing people skills but also stressing the need for, and value of, the practical training as recommended by Morrison and Laffin (1995). No individual trainee's performance was rated outstanding in the initial stages of the internship by any of the supervisors in any of the areas.…”
Section: Resultsmentioning
confidence: 84%
“…Morrison and Laffin (1995) questioned the value of practical teaching restaurants as experiential learning resources due to the limited extent to which most students are empowered to make management decisions in an 'unrealistic work environment' . Therefore, the experiences gained by interns in the work place are of great importance to them in gaining permanent employment.…”
Section: Hervementioning
confidence: 98%
“…Some authors in the area make reference to the traditional facility that is (or was) found in hospitality academic departments. Morrison and Laffin (1995, p. 26), while not referring directly to any traditional approach, emphasise that teaching restaurants and kitchens have 'long been established' as experiential learning forums, while Morrison (2003) states that in-house facilities are dominated by the 'traditional' training restaurant and kitchen configuration. Dutton and Farbrother (2005) discuss the closure of 'traditional training restaurants ' and Baker (1995, p. 21) continues to highlight the problems of credibility and cost associated with a 'production kitchen and public teaching restaurant'.…”
Section: Training Restaurants In Hospitality Educationmentioning
confidence: 99%
“…Research on institutions by Baker et al (1995) highlights the labour intensity and the call on departmental resources as negative aspects of operating training facilities. Morrison and Laffin (1995) Other options available to HE providers have been to outsource the operational element to further education providers (Baker et al, 1995). While there are advantages to this approach (highlighted by Baker et al), principally in terms of cost, there are also disadvantages both in terms of a loss of control and quality of teaching.…”
Section: Funding and Resourcing Training Facilities In Hospitality Edmentioning
confidence: 99%
See 1 more Smart Citation